AAV9-based gene therapy partially ameliorates the clinical phenotype of a mouse model of Leigh syndrome - Di Meo, I (Gene Ther, 2017)
Leigh syndrome (LS) is the most common infantile mitochondrial encephalopathy. No treatment is currently available for this condition. Mice lacking Ndufs4, encoding NADH: ubiquinone oxidoreductase iron-sulfur protein 4 (NDUFS4) recapitulates the main findings of complex I (cI)-related LS, including severe multisystemic cI deficiency and progressive neurodegeneration. In order to develop a gene therapy approach for LS, we used here an AAV2/9 vector carrying the human NDUFS4 coding sequence (hNDUFS4). We administered AAV2/9-hNDUFS4 by intravenous (IV) and/or intracerebroventricular (ICV) routes to either newborn or young Ndufs4(−/−) mice. We found that IV administration alone was only able to correct the cI deficiency in peripheral organs, whereas ICV administration partially corrected the deficiency in the brain. However, both treatments failed to improve the clinical phenotype or to prolong the lifespan of Ndufs4(−/−) mice. In contrast, combined IV and ICV treatments resulted, along with increased cI activity, in the amelioration of the rotarod performance and in a significant prolongation of the lifespan. Our results indicate that extraneurological organs have an important role in LS pathogenesis and provide an insight into current limitations of adeno-associated virus (AAV)-mediated gene therapy in multisystem disorders. These findings warrant future investigations to develop new vectors able to efficiently target multiple organs.